Moderasi Beragama dalam Al-Qur’an: Studi Tafsīr Nūrul Qur’ān Karya Allamah Kamāl Faqīh Īmānī - Lutfiyah, Lutfiyah; Shodiq, Muhammad (Mazalat: Jurnal Pemikiran Islam, 2025)
This research is based on a religious phenomenon in society where many religious practices lead to acts of intolerance (intolerance) and extremism (very extreme behavior), Ifrat (exaggeration), and Tafrith (ignoring or underestimating). Therefore, research on religious moderation is urgent and finds relevance amidst the onslaught of religious beliefs that are considered deviant. This research focuses on two objectives, namely exploring the concept of religious moderation in Allamah Kamāl Faqīh Īmānī’s Tafsīr Nūrul Qur’ān and its implications in the context of religious social life in Indonesia. This research is based on a literature review using primary and secondary sources. The method in this research is descriptive-analytical. The finding point of this research lies in the concept of religious moderation in Tafsīr Nūrul Qur’ān and its implications in the context of socio-religious life in Indonesia, that so far there has been no similar research on this theme. The results of this research can be concluded in two points as follows: first, religious moderation in Tafsīr Nūrul Qur’ān is based on the words wasaṭ (middle) and al-‘adl (fair). Wasaṭ and al-‘adl in the interpretation of Tafsīr Nūrul Qur’ān mean tawasut (moderate), tawazun (balanced), and Tasamuh (field-free). Second, the implications of religious moderation in Tafsīr Nūrul Qur’ān on religious social life can be formulated in three points; The first is the idea of ​​freedom of religion and belief, the second is building religious tolerance, and the third is building a perspective of peace and harmony among religious communities.